Church Union Movement and the Establishment of the “United Church of Christ in Japan” - Ziming Wang (Religions)
The establishment of the United Church of Christ in Japan (nihon kirisuto kyōdan 日本基督教団) marked the culmination of the Church Union Movement in Imperial Japan. Although the Church Union Movement can be traced back to the Meiji era, no significant breakthroughs were made until 1939 due to the refusal of some denominations. In this article, I aim to clarify the process and causes behind the formation of the united church, while also attempting to understand the interaction pattern between the State and Christianity under an increasing wartime totalitarian regime. In April 1939, the Diet passed the Religious Organizations Law (syūkyō dantai hō 宗教団体法), a bill aimed at strengthening state control over religions, which required Christian denominations to establish religious organizations. With the war intensifying Japan’s antagonism toward Western countries, Christianity as a foreign religion faced progressive attacks from the nationalist sects. Some denominations, like the Salvation Army, were accused of espionage due to their international connections and were monitored by gendarmerie (kenpeitai 憲兵隊). Facing harsh pressure, Christians sought to project a patriotic image, ultimately leading to the formation of the United Church as a survival strategy amidst a hostile social-political environment.